Health outcomes of the Bolsa Família program among Brazilian Amazonian children - Katherine J Ford; Barbara Hatzlhoffer Lourenço; Fernanda Cobayashi; Marly Augusto Cardoso (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE One of the primary objectives of Brazil's conditional cash transfer program, Bolsa Família, is to break the intergenerational transmission of poverty by improving human capital via conditionalities. In this study, we hypothesized that health indicators of Bolsa Família participants would be comparable to those of other local children who were nonparticipants after two years of follow-up in the city of Acrelândia, Acre state, Western Brazilian Amazon. METHODS Data from a population-based longitudinal study were analyzed to examine school enrollment, vaccination coverage, height and body mass index for age z-scores, and biomarkers of micronutrient deficiencies (iron and vitamin A) between Bolsa Família participants (n = 325) and nonparticipants (n = 738). RESULTS Out of 1063 children 10 years and younger included in the 2007 baseline survey, 805 had anthropometric measurements and 402 had biochemical indicators in the 2009 follow-up survey. Prevalence rate ratio (PRR) for non-enrollment in school at 4 years of age was 0.58 (95%CI: 0.34-1.02) when comparing Bolsa Família participants with nonparticipants. No difference was found for vaccination coverage, which was insufficient for most vaccine-preventable diseases. Bolsa Família participants were less likely to show a positive change in body mass index for age z-scores compared with nonparticipants (PRR = 0.81, 95%CI: 0.70-0.95), while a positive change in height for age z-scores was similar in the groups. No differences in micronutrient deficiencies were found between groups after 2 years. CONCLUSIONS Early school enrollment and consistent nutritional indicators between Bolsa Família participants and nonparticipants suggest Bolsa Família was facilitating similarities between groups over time.